Factors contributing to the underdiagnosis of hereditary transthyretin amyloidosis (hATTR) in Black patients - Hagerty KJ; Rosen AR; Heyward A; Ali N; Jeffreys B; Brown EE; Demo EM; Guan Y; Ogunniyi MO; Morris AA; Bhatt KN (Journal of Community Genetics, 2026)

Green-Synthesized Silver Nanoparticles Enhance Soybean Tolerance to Cadmium through Redox Regulation and Metabolic Reprogramming - Shifa Shaffique; Muhmmad Farooq; Muhmmad Saleem Khan; Ali Umar; Muhammad Aaqil Khan; Sang-Mo Kang; In-Jung Lee (Journal of Soil Science and Plant Nutrition, 2026)

Design, Synthesis and Biological Activity of Pyridine-Containing Aryl Urea Derivatives - Ali Dai; You Mo; Junyan Xu; Xiong Zhang; Yimin Ding; Liusheng Duan; Weiming Tan (Journal of Plant Growth Regulation, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

A candidate multi-epitopes vaccine against encephalomyocarditis virus confers protection in mice - Hongshan Li; Rongrong Cheng; Pingan Dong; Yongfang Chen; Rongqian Mo; Jiayu Yue; Dianyu Li; Yanmei Yang; Amjad Ali; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Optimizing application strategies of prohexadione-calcium·uniconazole composite regulator to improve lodging resistance and grain yield in rice cultivation in East China - Dengke Ma; Yimin Ding; Yifan Liu; Lin Du; You Mo; Ali Dai; Junyan Xu; Dalu Gu; Liusheng Duan; Weiming Tan (Field Crops Research, 2025)

Isolation, Structure, and Biological Activities of Exopolysaccharides from Actinomycetes: A Review - Xiao-Lian Wei; Song-Yi Mo; Rola Ali-Saeed; Hong Zeng (Current Microbiology, 2025)

New approach for the numerical analysis of stiffened deep cement mixing columns and piles in coastal engineering through 1D elements - Abolfazl Eslami; Ali Arjmand; Arman Ardehe; Amirhossein Ebrahimipour; Masoud Nobahar; Pin-Qiang Mo (Ocean Engineering, 2024)

Taxonomic and functional changes in wheat rhizosphere microbiome caused by imidazoline-based herbicide and genetic modification - Farman Ali; Zhaocheng Tang; Gangao Mo; Baolong Zhang; Xitie Ling; Zeyu Qiu (Environmental Research, 2024)

Modulation of maize growth, yield and soil enzymes activities by introducing wheat straw mulching and tillage practices - Shah Fahad; Imad Ali; Inzamam Hussain; Diyan Ahmad; Shah Saud; Khadim Dawar; Subhan Danish; Rahul Datta; Shah Hassan; Haitao Liu; Matthew Tom Harrison; Ke Liu; et al. (Plant and Soil, 2024)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Metabolomic profiling and antioxidant potential of three fungal endophytes derived from Artemisia annua and Medicago sativa - Ahmed M. Sayed; Noheir H. Sherif; Ahmed O. El-Gendy; Yara I. Shamikh; Asmaa T. Ali; Eman Zekry Attia; Mo'men H. El-Katatny; Basma Ali Khalifa; Hossam M. Hassan; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Application of an improved multifractal detrended fluctuation analysis approach for estimation of the complexity of daily precipitation - Liangliang Zhang; Heng Li; Dong Liu; Qiang Fu; Mo Li; Muhammad Abrar Faiz; Shoaib Ali; Muhammad Imran Khan; Tianxiao Li (International Journal of Climatology, 2021)
Affected by climate change and high‐intensity human activities, the precipitation series is characterized by nonlinear complex fluctuations. In order to accurately quantify the precipitation complexity, the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method was introduced to address the shortcomings of the traditional multifractal detrended fluctuation analysis (MFDFA), and the CEEMDAN‐MFFA method was proposed to explore the spatiotemporal variability and possible causes of precipitation complexity in Northeast China (NEC). The results showed that the traditional MFDFA method generally overestimated precipitation complexity. However, the CEEMDAN‐MFFA method improved the accuracy and reliability of precipitation complexity analysis. Daily precipitation series in NEC were characterized by multifractal with high uncertainty and anti‐persistence. The lowest precipitation complexity was 0.573, which appeared in Qian'an, Jilin Province, and the highest precipitation complexity was 1.108, which appeared in the Boketu, Inner Mongolia. The cities with high complexity of daily precipitation are sporadically distributed in the three provinces of Heilongjiang, Jilin and Liaoning. The average complexity is ~0.892, accounting for 22.5% of the total administrative districts. The complexity of daily precipitation showed a statistically insignificant downward trend with time. The precipitation dynamics structure in the southeast and northwest of the study area was complex, and the precipitation was less predictable than other regions. However, the precipitation dynamics structure was relatively simple and the precipitation was easily predictable in the northeastern, central and southwestern regions. Elevation, topographic relief, changes in water area, forest area and agricultural production were the main influencing factors for the differences in precipitation complexity. Results also revealed that increasing the area of forestland by means of protecting and breeding forests, via regulation of the forest ecosystems to alleviate the complex precipitation process will become a reliable approach to cope with nonstationary precipitation.

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Endophytic fungus Paecilomyces formosus LHL10 produces sester-terpenoid YW3548 and cyclic peptide that inhibit urease and α-glucosidase enzyme activities - Saqib Bilal; Liaqat Ali; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Sang-Mo Kang; Sang-Kuk Kim; In-Jung Lee (Archives of Microbiology, 2018)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Assessment of relevant fungal species in clinical solid wastes - Efaq Ali Noman; AA Al-Gheethi; Nik Norulaini Nik Ab. Rahman; H Nagao; MO Ab. Kadir (Environmental Science and Pollution Research, 2016)